Measuring organisational routines: a systematic review - Pavlov, Andrey (Cranfield University, 2006)
This dissertation employs the systematic review method to review the literature informing the question of using performance measurement to drive strategy execution. The narrative review outlines the location of this issue within the relevant domains of literature and is used to formulate the questions for the systematic review. The latter are formulated to reflect two major approaches to using measurement for strategic management purposes - measuring to challenge strategic assumptions and inform subsequent intervention and measuring to drive localised strategic learning. Learning is conceptualised as continuous change in organisational routines, where the latter provide a “window” to the firm’s strategy by the virtue of being the constituent parts of dynamic capabilities. The systematic review follows the structure suggested by Cranfield School of Management and outlines the sequence of actions taken during the review process. It provides a record of the decisions taken and outside input received during the process. The evidence found through the systematic review leads to several conclusions. First, the inadequate level of research into the measures of routines precludes measurement from being used for evaluating routines to inform subsequent intervention. Measures of routines need to be systematised, better understood and better operationalised before this application of measurement becomes possible as an independent strategic management approach. A first step in this direction is offered by proposing a classification of measures of organisational routines. Understanding changes in routines as learning that can be influenced by performance measurement offers a greater potential. It is suggested that while learning is stimulated by performance feedback and takes place through routines, it can be influenced strategically through the use the feedforward function of measurement. The results of the findings from the systematic review are integrated into a coherent framework, on the basis of which several avenues for further research are suggested.